1980
DOI: 10.1177/014107688007301008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Atropine and Glycopyrrolate on various End-Organs1

Abstract: Summary: Atropine and glycopyrrolate (glycopyrronium bromide), a quaternary ammonium drug, were evaluated in volunteers following intramuscular administration with respect to effects on various end-organs with cholinergic innervation. Glycopyrrolate appears to be five to six times more potent than atropine in its antisialogogue effect and also exhibits a selective, though prolonged, effect on salivary secretion and sweat gland activity. It has minimal cardiovascular, ocular and central nervous system effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Anticholinergic drugs are increasingly being used in the premedication phase before small surgery 19 because of their capacity to reduce secretions, protect against vagal stimulation 20 , facilitate tracheal intubation, and provide a better visualization 21 . Glycopyrrolate is generally preferred to atropine because of its ability to inhibit saliva production and its more favorable safety profile (being characterized by a lower risk of cardiovascular or central nervous system adverse events) 22 , 23 . Moreover, premedication with glycopyrrolate may reduce sore throat after general endotracheal anesthesia, post-operative catheter-related bladder discomfort following general anesthesia, and the frequency and intensity of nausea, as well as the severity of hypotensive episodes during spinal anesthesia 24 – 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Anticholinergic drugs are increasingly being used in the premedication phase before small surgery 19 because of their capacity to reduce secretions, protect against vagal stimulation 20 , facilitate tracheal intubation, and provide a better visualization 21 . Glycopyrrolate is generally preferred to atropine because of its ability to inhibit saliva production and its more favorable safety profile (being characterized by a lower risk of cardiovascular or central nervous system adverse events) 22 , 23 . Moreover, premedication with glycopyrrolate may reduce sore throat after general endotracheal anesthesia, post-operative catheter-related bladder discomfort following general anesthesia, and the frequency and intensity of nausea, as well as the severity of hypotensive episodes during spinal anesthesia 24 – 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Arbouw et al studied the efficacy of glycopyrrolate, an anti‐cholinergic that does not cross the blood–brain barrier in considerable amounts 33 . Twenty three participants took part in a crossover trial that compared 1 mg of glycopyrrolate taken three times daily against placebo.…”
Section: Resultsmentioning
confidence: 99%
“…18,23,26,29 Arbouw et al studied the efficacy of glycopyrrolate, an anticholinergic that does not cross the blood-brain barrier in considerable amounts. 33 Twenty three participants took part in a crossover trial that compared 1 mg of glycopyrrolate taken three times daily against placebo. A sialorrhoea scoring scale was used to assess efficacy and significant improvements were found in the group treated with glycopyrrolate.…”
Section: Reviewmentioning
confidence: 99%
“…An older study demonstrated differences in end-organ effects between atropine and glycopyrrolate. Glycopyrrolate had a selective and prolonged inhibitory effect at salivary and sweat glands, with minimal cardiovascular, ocular, and CNS effects compared to atropine [ 40 ].…”
Section: Preventionmentioning
confidence: 99%